The effects of the self-assessment system on the tax compliance costs of small and medium enterprises in Malaysia - Abdul Jabbar, Hijattulah; Pope, Jeff (Australian Tax Research Foundation, 2008)
This paper briefly discusses the importance of Small and Medium Enterprises (SMEs) in Malaysia. The concepts of tax compliance costs and prior compliance costs studies, both internationally and in Malaysia, are succinctly reviewed. The methodology used in the current estimates, based on the traditional postal survey questionnaire technique, is presented. The main part of the paper presents current (2006 survey year) estimates of the compliance costs of taxation of Malaysian SMEs and compares these estimates with earlier (1999) estimates. The findings clearly suggest that SME compliance costs over the period have fallen, contrary to the general presumption. The introduction of the Self-Assessment System (SAS) in 2001 and the subsequent simplification measures taken by the Inland Revenue Board are probably major explanatory factors. However, the major Asian financial crisis during the pre-SAS study may also have encouraged SMEs to significantly overstate their compliance costs at that time. The usual regressive pattern of compliance costs is confirmed, and estimates, in terms of business size and other characteristics, internal/external costs, and computational/planning costs are analysed. This research approach follows that of earlier studies in Australia (by Pope et al), Malaysia, Singapore and Hong Kong (by Ariff et al)